Challenges and Strategies Used of Thai Students in Indonesian Language Learning in the BIPA Program: A case of EMI - Nuro Sabuela; Mauly Halwat Hikmat; Nur Hidayat (Universitas Islam Negeri Palopo, 2026)
This study aims to explore the challenges faced by Thai students and the strategies they employ in Indonesian language learning in the BIPA program at Universitas Muhammadiyah Surakarta (UMS), where English is used as a Medium of Instruction (EMI). The increasing use of EMI in multilingual educational settings has created both opportunities and challenges for international students who are learning a new language through another foreign language. The research focuses on analyzing the types of learning difficulties students experience when EMI is used as the instructional language and the factors contributing to these challenges. A qualitative case study research methodology was employed, collecting data through semi-structured interviews and classroom observations with five Thai students participating in the BIPA program. The interviews were conducted to explore students’ perceptions of their learning experiences, while classroom observations were used to examine how students interacted with the lecturer and responded to EMI during classroom activities. The result indicated that students faced language challenges including limited English language proficiency, difficulty processing multiple languages simultaneously, and difficulty understanding explanations from English-speaking instructors. Classroom observations also revealed that students frequently used online translation tools and sought peer assistance to better understand lessons. In several situations, students relied on their classmates to clarify instructions and translate unfamiliar vocabulary into their native language. Despite these challenges, students developed various learning strategies such as using translation applications, collaborating with peers, and self-studying vocabulary. These strategies demonstrate students’ ability to adapt to a multilingual learning environment and actively manage their language learning process. These findings suggest that while EMI may create language barriers in multilingual classrooms, appropriate teaching strategies and peer support can help students cope with these challenges and enhance their learning experiences in the BIPA program.